Analisis Rasch Kemampuan Pemodelan Matematik pada Learning Obstacle dan Desain Didaktis Pembelajaran Etnomatematika Sunda Siswa Kelas II Sekolah Dasar - Rahmanita, Aulia; Supriadi, Supriadi (Didaktika, 2021)
This study aimed to analyze using Rasch model through the Winstep application on learning obstacle data and Sundanese ethnomathematical didactic design using Engklek game to measure the mathematical modeling ability of students in second grade of Elementary School. Culture-based mathematics learning can increase students' understanding, especially traditional games. One of them is Engklek game which can be developed as a mathematical modeling learning design for children. The indicators of mathematical modeling ability were simplification, mathematization, and problem-solving abilities. In the Rasch model, the researchers chase the output Item Measure to know the items level of difficulty, Item Fit Order to measure the level of items suitability in measuring the ability of mathematical modeling in students, Person Measure to determine the student's ability level to work on the test instrument and Summary Statistics as a summary of the overall statistics of the test instrument. This study was structured with a quantitative approach using quantitative descriptive methods. The data analyzed were learning obstacle data totaling 61 data, initial didactic design data as many as 28, and didactic design revision data totaling 9 data. From the data, it was found that all items were appropriate in measuring students' mathematical modeling abilities, but there were still things that needed to be evaluated in the questions' interaction with students. The student's ability in each mathematical modeling indicator varies and was grouped into the “high" ability level of 27 students, 35 students of “mid” level and 27 “low” level students, and 3 students groups. The results of this analysis could be a validation that the learning carried out was feasible and has the potential to succeed in increasing students' modeling competence